Diffusion of oxygen in hypostoichiometric uranium dioxide nanocrystals. A molecular dynamics simulation - K. A. Nekrasov; A. E. Galashev; D. D. Seitov; S. K. Gupta (Chimica Techno Acta)
A molecular dynamic simulation of diffusion of intrinsic oxygen anions in the bulk of hypostoichiometric UO2-x nanocrystals with a free surface was carried out. The main diffusion mechanism turned out to be the migration of oxygen by the anionic vacancies. It is shown that in the range of values of the non-stoichiometry parameter 0.05 £x £ 0.275 the oxygen diffusion coefficient D is weakly dependent on temperature, despite the uniform distribution of the vacancies over the model crystallite. The reliable D values calculated for the temperature T = 923 K are in the range from 3×10-9 to 7×10-8 cm2/s, in quantitative agreement with the experimental data. The corresponding diffusion activation energy is in the range from 0.57 eV to 0.65 eV, depending on the interaction potentials used for the calculations.